Analysis of cost and outcomes in bony versus soft tissue midface free flap reconstruction. Issue 8 (6th June 2022) - Alnemri, Angela; Philips, Ramez; Sussman, Sarah; Xu, Vivian; Givens, Alyssa; Patel, Anjali; Swendseid, Brian; Agarwal, Aarti; Keith, Scott; Shimada, Ayako; Selman, Yamil; Cognetti, David M.; et al.
Abstract: Background: Outcomes and cost of soft tissue versus bony midface free flap reconstruction (MR) with and without virtual surgical planning (VSP) were evaluated. Methods: Retrospective review of MR including ischemic time (IT), operative duration (OD), length of stay (LOS), and total cost (TC). Eighty‐one soft tissue and 76 bony MR (VSP = 23) were reviewed. Results: Bony MR was used for higher complexity defects ( p  = 0.003) and was associated with higher IT ( p  < 0.001), OD ( p  < 0.001), LOS ( p  = 0.032), and TC ( p  < 0.001). VSP was associated with a mean 111.2 ± 37.9 minute reduction in OD ( p  = 0.004) compared to non‐VSP bony flaps. VSP was associated with higher itemized cost, but no increase in TC ( p  = 0.327). Conclusions: Bony MR was used for higher complexity MR and was associated with increased TC, LOS, OD, and IT. VSP shortened OD with no significant increase in TC.